2012
DOI: 10.1021/bi3007753
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Studies of the Lysine Riboswitch Reveal Effector-Dependent Conformational Dynamics of the Aptamer Domain

Abstract: The lysine riboswitch is a cis-acting RNA genetic regulatory element found in the leader sequence of bacterial mRNAs coding for proteins related to biosynthesis or transport of lysine. Structural analysis of the lysine-binding aptamer domain of this RNA has revealed that it completely encapsulates the ligand and therefore must undergo a structural opening/closing upon interaction with lysine. In this work, single-molecule fluorescence resonance energy transfer (FRET) methods are used to monitor these ligand-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 63 publications
(166 reference statements)
10
68
0
Order By: Relevance
“…Typically, a riboswitch aptamer domain is site-specifically labeled with both donor and acceptor fluorophores for FRET, then attached to a glass (or quartz) surface via linker chemistry (Figure 2) [51]. To date, lysine [52], SAM class I [53], SAM class II [54], guanine [55], adenine [5658], TPP [59], c-di-GMP class I [60], and preQ 1 class I & II riboswitches [61, 62] have been explored using smFRET methodologies (section 4 ).…”
Section: Single-molecule Methodsmentioning
confidence: 99%
“…Typically, a riboswitch aptamer domain is site-specifically labeled with both donor and acceptor fluorophores for FRET, then attached to a glass (or quartz) surface via linker chemistry (Figure 2) [51]. To date, lysine [52], SAM class I [53], SAM class II [54], guanine [55], adenine [5658], TPP [59], c-di-GMP class I [60], and preQ 1 class I & II riboswitches [61, 62] have been explored using smFRET methodologies (section 4 ).…”
Section: Single-molecule Methodsmentioning
confidence: 99%
“…For the SAM-I riboswitch, a dynamic three-state exchange process was uncovered where the ligand-free state exhibited unfolding dynamics in the milliseconds regime and the most compacted fold was frozen in the presence of ligand (43). For the lysine riboswitch, smFRET was used to measure the opening/closing rate constants for the aptamer domain as well as the lysine dissociation constant (9). Although these studies have provided an important foundation for understanding the relationship between riboswitch dynamics, ligand binding and gene expression regulation, continued, indepth investigations along these lines of pursuit are greatly needed.…”
Section: Large Structurally Complex Riboswitches With Pseudoknots Andmentioning
confidence: 99%
“…In this form of regulation, the target mRNA typically undergoes a structural change in response to metabolite binding (5)(6)(7)(8)(9). These mRNA elements have thus been termed "riboswitches" and generally include both a metabolite-sensitive aptamer subdomain and an expression platform.…”
mentioning
confidence: 99%
“…66,78 Fiegland and colleagues showed that ligand binding promotes a population shift into a previously unoccupied high-FRET state that corresponds to the close association of the bottom stem-loops, consistent with the 'ordering' definition of IF. 79 In addition, as the concentration of lysine increases, the folding rate also increases, 79 while the unfolding rate is insensitive to the ligand concentration. This is the definition of IF according to the kinetic/energetic picture.…”
Section: Insights Into Aptamer-ligand Interactions From Single-molecumentioning
confidence: 99%
“…The famous picture of the folding energy landscape is, after all, highdimensional, and dozens of environmental factors, including Mg 2+ and the ligand, influence it. While some riboswitches like lysC have a well-defined mechanism across a wide range of environments, 79 bsu can bind its ligand at different stages of folding, 84 changing its path to the native state dramatically, while env8 86 and the adenine Please do not adjust margins Please do not adjust margins …”
Section: +mentioning
confidence: 99%